2010
DOI: 10.1182/blood-2009-12-257485
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide DNA methylation analysis reveals novel targets for drug development in mantle cell lymphoma

Abstract: IntroductionMantle cell lymphoma (MCL) is an aggressive and mostly incurable B-cell malignancy accounting for 5% of non-Hodgkin lymphomas (NHLs). MCL arises from naive B cells (NBCs) in the mantle zone of lymph node follicles and is characterized by the t(11,14) chromosomal translocation leading to overexpression of cyclin D1 (CCND1). 1 However, murine models overexpressing CCND1 in the absence of other oncogenes, such as MYC, do not develop lymphoma, 2 implying that additional pathogenic mechanisms are involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
102
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(108 citation statements)
references
References 46 publications
3
102
2
1
Order By: Relevance
“…[3][4][5][6] NOTCH1 activation may contribute to the development of other hematopoietic malignancies, including chronic lymphocytic leukemia [7][8][9] and mantle cell lymphoma. 10,11 These findings support the continued development of NOTCH inhibitors as cancer therapeutics.…”
Section: Introductionmentioning
confidence: 62%
“…[3][4][5][6] NOTCH1 activation may contribute to the development of other hematopoietic malignancies, including chronic lymphocytic leukemia [7][8][9] and mantle cell lymphoma. 10,11 These findings support the continued development of NOTCH inhibitors as cancer therapeutics.…”
Section: Introductionmentioning
confidence: 62%
“…QPCT, which encodes a glutaminyl cyclase (Fischer and Spiess, 1987;Pohl et al, 1991), is frequently methylated in malignant melanoma (Muthusamy et al, 2006). Functional PCDH8 is frequently lost in breast cancer through both mutation and promoter methylation (Yu al., 2008), and also methylated in mantle cell lymphoma (Leshchenko et al, 2010). FBN2 and the related gene FBN1 encode large modular extracellular matrix glycoproteins, which are the key components of human microfibrils (Zhang et al, 1994).…”
Section: Ct Bstu1mentioning
confidence: 99%
“…There is increasing evidence that protocadherins can function as tumour suppressors. Protocadherins 10 and 20 are epigenetically silenced in nasopharyngeal and lung cancers (Imoto et al, 2006;Ying et al, 2006), and recently it has been reported that PCDH8 is methylated in mantle cell lymphoma and breast cancer (Yu et al, 2008;Leshchenko et al, 2010). Yu et al found that reexpressing wild-type PCDH8 in a breast cancer cell line inhibited cell migration.…”
Section: Ct Bstu1mentioning
confidence: 99%
“…In that regard, chromosomal alterations and nongenetic modifications resulting in the constitutive activation of pro-oncogenic signals (for example, NF-kB, Notch, PI3K/AKT/mTOR, and Wnt) and/or deregulation of DNA repair and apoptotic pathways and genes (for example, AKT, BCL2, MCL1) have been found in subsets of MCLs, providing additional levels of plasticity in the genesis and progression of the disease. 1,[3][4][5][6][7][8][9][10][11] Of particular interest is the canonical Wnt pathway that has a crucial role in normal hematopoiesis and whose aberrant activation, long known to drive tumorigenesis in solid tumors, has also been involved in a number of hematological malignancies, including MCLs. 3,5,6,[12][13][14][15][16][17][18][19]20 In addition to gain-of-function mutations of intracellular components of the Wnt pathway, overexpression of Wnt receptors and ligands or downregulation of Wnt inhibitors through nongenetic modifications are also common.…”
mentioning
confidence: 99%
“…3,5,6,[12][13][14][15][16][17][18][19]20 In addition to gain-of-function mutations of intracellular components of the Wnt pathway, overexpression of Wnt receptors and ligands or downregulation of Wnt inhibitors through nongenetic modifications are also common. 3,[5][6][7]21 Short-lived response and development of resistance to first-line immunochemotherapy are major challenges in MCL and new therapeutic strategies are being developed. 1,22,23 Constitutive Wnt signaling associates to increased cellular proliferation and higher resistance to apoptosis and chemotherapy in subsets of leukemias and lymphomas and established cell lines derived from them, including MCLs.…”
mentioning
confidence: 99%